2020
DOI: 10.2217/rme-2020-0040
|View full text |Cite
|
Sign up to set email alerts
|

Combination of Preconditioned Adipose-Derived Mesenchymal Stem Cells and Platelet-Rich Plasma Improves the Repair of Osteoarthritis in Rat

Abstract: Aim: To observe the combined effect of platelet-rich plasma (PRP) and preconditioned adipose-derived mesenchymal stem cells (ADMSCs) on the injured articular cartilage of the rat. Materials & methods: Animals in the study received an intra-articular injection of PRP and preconditioned ADMSCs, both in combination and separately. The response to therapeutic intervention was evaluated by inflammatory markers, proteoglycans content, chondrogenesis and gene expression analyses. Results: The combined therapy res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Moreover, in vitro studies alone cannot mirror the complexity of the joint environment response to PRP intra-articular injections, and in vivo studies are needed to confirm the suggested detrimental effects of leukocytes in PRP. 1 In a mouse model of posttraumatic knee OA, Jayaram et al 23 compared the intra-articular injection of LR-PRP and LP-PRP to assess the potential to alter disease progression. The authors observed controversial results, indicating better protection from cartilage volume loss at phase-contrast computed tomography analysis after LP-PRP, while LR-PRP demonstrated better protection from thermal hyperalgesia; in addition, the histologic evaluation did not show differences in terms of cartilage degeneration and synovitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in vitro studies alone cannot mirror the complexity of the joint environment response to PRP intra-articular injections, and in vivo studies are needed to confirm the suggested detrimental effects of leukocytes in PRP. 1 In a mouse model of posttraumatic knee OA, Jayaram et al 23 compared the intra-articular injection of LR-PRP and LP-PRP to assess the potential to alter disease progression. The authors observed controversial results, indicating better protection from cartilage volume loss at phase-contrast computed tomography analysis after LP-PRP, while LR-PRP demonstrated better protection from thermal hyperalgesia; in addition, the histologic evaluation did not show differences in terms of cartilage degeneration and synovitis.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in vitro studies alone cannot mirror the complexity of the joint environment response to PRP intra-articular injections, and in vivo studies are needed to confirm the suggested detrimental effects of leukocytes in PRP. 1…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, PRP has an anabolic effect on both MSCs and chondrocytes, assisting in proliferation, inhibiting deregulation, and supporting matrix development, which further maintains appropriate chondrocyte and stem cell development [ 32 ]. This combination leads to a reduction in TNF-α and IL-6 concentration, together with an increase in proteoglycans concentration in articular cartilage [ 33 ].…”
Section: Bioregenerative Therapies In Osteoarthritismentioning
confidence: 99%
“…Moreover, IA injection of ADSCs combined with arthroscopic debridement in patients with early knee OA has reported good results in terms of pain and function [ 79 ]. In addition, a combination of ADSCs with PRP in a rat model has shown that PRP potentiates the effect of ADSCs in damaged articular cartilage [ 33 ]. Recently, Okamoto-Okubo et al reported the best results with allogenic ADSCs over PRP in dogs with bilateral degenerative hip joint disease [ 80 ].…”
Section: Bioregenerative Therapies In Osteoarthritismentioning
confidence: 99%
“…Ahmad et al in 2020 [50] published an experimental study on rats comparing the efficacy of PRP, ADMSCs, and their combination on a surgically induced osteoarthritic knee. They concluded that interleukin-6 expression is significantly reduced in the combined group, with a significantly higher proteoglycan content compared to the other groups.…”
Section: Osteoarthritismentioning
confidence: 99%